The use of actigraphy in the monitoring of sleep and activity in ADHD: A meta-analysis. (April 2016) - De Crescenzo, Franco; Licchelli, Serena; Ciabattini, Marco; Menghini, Deny; Armando, Marco; Alfieri, Paolo; Mazzone, Luigi; Pontrelli, Giuseppe; Livadiotti, Susanna; Foti, Francesca; Quested, Digby; Vicari, Stefano
Summary: Attention deficit/hyperactivity disorder (ADHD) is the most common neurobehavioral disorder of childhood. There is an increasing need to find objective measures and markers of the disorder in order to assess the efficacy of the therapies and to improve follow-up strategies. Actigraphy is an objective method for recording motor activity and sleep parameters that has been used in many studies in ADHD. Our meta-analysis aimed to assess the current evidence on the role of actigraphy in both the detection of changes in motor activity and in sleep patterns in ADHD. A systematic review was carried out to find studies comparing children with unmedicated ADHD versus controls, using actigraphic measures as an outcome. The primary outcome measures were "sleep duration" and daytime "activity mean". As secondary outcome measures we analyzed "sleep onset latency", "sleep efficiency" and "wake after sleep onset". Twenty-four studies comprising 2179 children were included in this review. We show evidence that ADHD compared to typically developing children present a higher mean activity during structured sessions, a similar sleep duration, and a moderately altered sleep pattern. This study highlights the role of actigraphy as an objective tool for the ambulatory monitoring of sleep and activity in ADHD.